Prevalence, subtypes, and correlates of nocturia in the symptoms of Lower Urinary Tract Dysfunction Research Network cohort. Issue 4 (6th April 2020) - Clemens, J. Quentin; Wiseman, Jonathan B.; Smith, Abigail R.; Amundsen, Cindy L.; Yang, Claire C.; Bradley, Megan S.; Kirkali, Ziya; Agochukwu, Nnenaya Q.; Cameron, Anne P.
Abstract: Aims: We determined the prevalence, severity, and correlates of nocturia in a large clinical cohort of patients. Methods: Patients presenting with lower urinary tract symptoms (LUTS) completed 3‐day bladder diaries. Nocturia was quantified based on the mean number of nighttime voids documented over the 3 days. Nocturia subtypes (global polyuria, nocturnal polyuria [NP], reduced global bladder capacity, and reduced nocturnal bladder capacity) were assessed. Bother due to nocturia was measured by the LUTS Tool. Sleep quality was assessed with the Patient‐Reported Outcomes Measurement Information System Sleep Scale. Multivariable multinomial regression was used to explore patient characteristics associated with nocturia. Results: In 502 participants with analyzable diaries (285 men and 217 women), the mean number of nocturia episodes over 3 days was 0 in 103 (20.5%), >0 to <1 in 151 (20.1%), 1 to <2 in 165 (32.9%), and ≥2 in 83 (16.5%). Sixty‐seven percent of the participants with nocturia ≥1 reported significant bother from their nocturia. NP was the most common nocturia subtype and was present in 17% of those with nocturia = 0, 40% of those with nocturia >0 to <1, 65% of those with nocturia 1 to <2%, and 77% with nocturia 2+. Higher degrees of nocturia were associated with male sex, greater sleep disturbance, and a higher likelihood of exhibiting multiple nocturia subtypes. Conclusions: Nocturia ≥1 occurred in 49% of LUTS patients and caused significant bother in the majority of them. The most common subtype was NP, but a substantial proportion of patients exhibited additional characteristics.